Applying Lean Methodology to Optimize Patient Flow in JKN Outpatient Services: Evidence from a Cardiac Hospital in Indonesia - Shiddieq, Hashbi Ash; Soenaria, Syaiful Rachman; Handoyo, Sofik (GoAcademica Research & Publishing, 2025)
This study aims to investigate patient flow inefficiencies in the JKN outpatient department of a cardiac hospital and evaluate how Lean tools specifically process mapping and root cause analysis can enhance service efficiency and reduce waiting times. A qualitative single-case study design was employed using Lean methodology. Data were collected through direct observation, unstructured staff interviews, and A3 problem-solving documentation. Process mapping and value stream mapping (VSM) were used to analyze the current patient journey, while Ishikawa diagrams facilitated root cause identification. The study identified significant delays in the registration, consultation, and pharmacy stages, driven by manual processes, limited specialist availability, and fragmented workflows. Key contributors to overcrowding included early patient arrivals, inadequate appointment scheduling, and lack of digital integration. A future-state value stream map was developed, incorporating electronic queue registration and e-prescribing systems to streamline service flow and optimize resource utilization. The study demonstrates the applicability of Lean principles in high-demand outpatient settings and offers a replicable framework for healthcare organizations seeking to reduce service delays and improve patient throughput. It emphasizes the need for coordinated process redesign, digital innovation, and standardized performance metrics. This research contributes to the limited literature on Lean application in Indonesia’s public health insurance context (JKN) by integrating voice-of-process and voice-of-staff perspectives. The proposed Lean-based interventions are empirically grounded and aligned with national healthcare quality indicators, offering practical guidance for system-wide improvement.